Effects of a Syndrome-Specific Antibiotic Stewardship Intervention for Inpatient Community-Acquired Pneumonia. (1st September 2016) - Haas, Michelle K.; Dalton, Kristen; Knepper, Bryan C.; Stella, Sarah A.; Cervantes, Lilia; Price, Connie S.; Burman, William J.; Mehler, Philip S.; Jenkins, Timothy C.
Abstract : A syndrome-specific intervention to improve the management of community-acquired pneumonia in non-intensive care settings was associated with shorter treatment durations, less fluoroquinolone use, and a reduction in use of low-yield diagnostic tests. Abstract: Background. Syndrome-specific interventions are a recommended approach to antibiotic stewardship, but additional data are needed to understand their potential impact. We implemented an intervention to improve the management of inpatient community-acquired pneumonia (CAP) and evaluated its effects on antibiotic and resource utilization. Methods. A stakeholder group developed and implemented a clinical practice guideline and order set for inpatient, non-intensive care unit CAP recommending a short course (5 days) of a fluoroquinolone-sparing antibiotic regimen in uncomplicated cases. Unless there was suspicion for complications or resistant pathogens, chest computed tomography (CT) and sputum cultures were discouraged. This was a retrospective preintervention postintervention study of patients hospitalized for CAP before (April 15, 2008–May 31, 2009) and after (July 1, 2011–July 31, 2012) implementation of the guideline. The primary comparison was the difference in duration of therapy during the baseline and intervention periods. Secondary outcomes included changes in use of levofloxacin, CT scans, and sputum culture. Results. One hundred sixty-six and 84 cases during the baseline and intervention periods, respectively, were included. From the baseline to intervention period, the median duration of therapy decreased from 10 to 7 days ( P < .0001). Prescription of levofloxacin at discharge decreased from 60% to 27% of cases ( P < .0001). Use of chest CT and sputum culture decreased from 47% to 32% of cases ( P = .02) and 51% to 31% of cases ( P = .03), respectively. The frequency of clinical failure between the 2 periods was similar. Conclusions. A syndrome-specific intervention for inpatient CAP was associated with shorter treatment durations and reductions in use of fluoroquinolones and low-yield diagnostic tests.